2016
DOI: 10.1590/s1679-45082016rb3582
|View full text |Cite
|
Sign up to set email alerts
|

Group A rotavirus gastroenteritis: post-vaccine era, genotypes and zoonotic transmission

Abstract: This article provides a review of immunity, diagnosis, and clinical aspects of rotavirus disease. It also informs about the changes in epidemiology of diarrheal disease and genetic diversity of circulating group A rotavirus strains following the introduction of vaccines. Group A rotavirus is the major pathogen causing gastroenteritis in animals. Its segmented RNA genome can lead to the emergence of new or unusual strains in human populations via interspecies transmission and/or reassortment events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(125 citation statements)
references
References 77 publications
(123 reference statements)
4
70
0
6
Order By: Relevance
“…In the population of animals studied the zoonotic transmission can be frequent, since the animals live in contact with humans and in precarious sanitary conditions. In Brazil, this genotype was described in animal and human populations in studies of Luchs et al [32]; Honma et al [67]; Araújo et al [68]; Mascarenhas et al [69] and Lorenzetti et al [70] such studies corroborate the importance of continuing to monitor genotypes to verify if uncommon strains or new strains are emerging and can infect animal populations or inter-species transmissions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the population of animals studied the zoonotic transmission can be frequent, since the animals live in contact with humans and in precarious sanitary conditions. In Brazil, this genotype was described in animal and human populations in studies of Luchs et al [32]; Honma et al [67]; Araújo et al [68]; Mascarenhas et al [69] and Lorenzetti et al [70] such studies corroborate the importance of continuing to monitor genotypes to verify if uncommon strains or new strains are emerging and can infect animal populations or inter-species transmissions.…”
Section: Discussionmentioning
confidence: 70%
“…Although the results of RVA have already been described globally [12,[23][24][25][26][27][28][29][30], in Brazil, the occurrence, diversity and role of rotavirus in these animals are still poorly studied, considering the large number of present species [4,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The wide host breadth of RVA strains indicated the potential of RVAs for interspecies transmission. Only one G10 strain was identified in the study, this strain is uncommon in human (Do et al, ; Luchs & Timenetsky Mdo, ) but are frequently found in animals, particularly in cattle, pigs and lambs (Ennima et al, ; Komoto et al, ; Madadgar, Nazaktabar, Keivanfar, Zahraei Salehi, & Lotfollah Zadeh, ; Mohamed, Mansour, El‐Araby, Mor, & Goyal, ; Rajendran & Kang, ). G10P[15] is an unusual combination but has previously been reported in a calf in India (Rajendran & Kang, ).…”
Section: Discussionmentioning
confidence: 95%
“…Ротавірусна інфекція також схильна до генералізації в організмі людини, призводячи до неврологічних ускладнень, які виявляються у 2-5 % випадків [19].…”
Section: оригінальні дослідження вступunclassified